Basal cell ameloblastoma: A rare histological variant of an uncommon tumor - Meela Sridhar; L Raja Bhaskar Reddy; Sagar Kharat; B S Mahesh; Lakshmi Gandi; Ashish Mahendra; Pankhuri Nigam; Parveen Grewal (Nigerian Journal of Surgery, 2015)
Ameloblastomas are an inscrutable group of oral tumors. Basal cell ameloblastoma is a rare variant of ameloblastoma with very few cases reported until date. The tumor is composed of more primitive cells and has less conspicuous peripheral palisading. It shows remarkable similarity to basal cell carcinoma, basal cell adenoma and intra-osseous adenoid cystic carcinoma. This report describes the case of a 27-year-old male with an ameloblastoma in the right posterior mandible. Orthopantomography computed tomography and finally histopathological examination directed us toward the confirmatory diagnosis of basal cell variant of ameloblastoma. Considering the rarity of the lesion and histological paradox regarding its diagnosis, we report here an interesting and rare case of basal cell ameloblastoma of the mandible with emphasis on differential diagnosis from other entities with basaloid differentiation having varying prognosis. After surgery, long-term follow-up at regular intervals is recommended as no sufficient statistical information regarding the behavior of this tumor is available.